Polycotylidae (Sauropterygia, Plesiosauria) from the La Colonia Formation, Patagonia, Argentina: Phylogenetic affinities of Sulcusuchus erraini and the Late Cretaceous circum-pacific polycotylid diversity - O'gorman, Jose Patricio (2022)
Polycotylids were a clade of short-necked plesiosaur that achieved a worldwide distribution and a peak of diversity during the Albian–Turonian, reaching the K/Pg mass extinction with a relative low diversity. One of the youngest polycotylids worldwide recorded is Sulcusuchus erraini, from Los Alamitos and La Colonia formations (Patagonia). Here, a new polycotylid specimen, also from Maastrichtian levels of the La Colonia Formation, is described; and the affinities of the new material and Sulcusuchus erraini are evaluated. Additionally, the phylogenetic position of Sulcusuchus erraini is reevaluated recovering Sulcusuchus erraini outside the Occultonectia, the latter comprising only Cenomanian–Turonian polycotylids. However, additional analysis indicate that the position of S. erraini is far from being well resolved.